2020
DOI: 10.1039/c9na00699k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced strength of nano-polycrystalline diamond by introducing boron carbide interlayers at the grain boundaries

Abstract: Polycrystalline diamond with high mechanical properties and excellent thermal stability plays an important role in industry and materials science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The hardness values were calculated by the equation H v = d −2 , where F and d represent the loading force and the mean value of the lengths of diagonals. [ 47,48 ] Standard DAC cell and PeCu cell with 200 µm flat culets were used for the in situ pressure‐dependent Raman and electrical conductivity measurements under compression of pressures ranging ambient to 61 GPa. Rhenium gaskets were pre‐indented to 25–30 µm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The hardness values were calculated by the equation H v = d −2 , where F and d represent the loading force and the mean value of the lengths of diagonals. [ 47,48 ] Standard DAC cell and PeCu cell with 200 µm flat culets were used for the in situ pressure‐dependent Raman and electrical conductivity measurements under compression of pressures ranging ambient to 61 GPa. Rhenium gaskets were pre‐indented to 25–30 µm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…To our best knowledge, the NPD samples in the present study exhibit the highest hardness in all the reported NPD materials synthesized by sintering nano/micro-sized diamond crystals under high pressure and high temperature. [13,15] More important, they are significantly harder than SCD and those NPD synthesized from fullerene and glassy carbon by HPHT. [6] For the synthesized NPD samples, more dislocations were created in the nanocrystals of SAND-1 sample during HPHT but the corresponding hardness is the lowest, indicating that the dislocations/structural defects in NPD is not responsible to the high hardness.…”
Section: Weakening Effects Of Nano Amorphous Carbonmentioning
confidence: 99%
“…This could also be used to understand why the sintered NPD composite could exhibit superhardness when a relatively soft component is added during HPHT sintering. [15,17]…”
Section: Weakening Effects Of Nano Amorphous Carbonmentioning
confidence: 99%
“…HPHT is the more effective method for preparation of AlB 2type TMdBs. HPHT can help to cross the high energy barrier and provide rapid cooling and quenching to retain metastable phase [76,[85][86][87][88][89][90][91][92]. Moreover, HP is advanced in forming bulk materials with high density.…”
Section: Synthesis and Basic Mechanical And Physical Propertiesmentioning
confidence: 99%